Suspicion and its Effects on Punishment (Hudood & Qisas) - Elham Mohammed Ali Tweir (My University, 2008)
Murder crimes and other deeds that require legal punishment are in fact dangerous crimes that threaten the whole existence of a society and its regime. Therefore, legislators have decided various definite punishments to be imposed on those who commit such crimes and considered them as legislative punishments that can't be cancelled or quitted or dealt with by means of mediation settlements. Yet, in spite of all these strict regulation in defining and executing punishments, legislators decided in favor of some precautional rules and controls that restrict the execution of punishments, unless those crimes are very surely committed completely and clearly which make them deserve execution. One of these priority rules is that which claims: Punishments might be detained (dropped) by Suspicions This rule is agreed upon by most legislators except for (Al- Dhahiriya) group, as it (the rule) depends on deeds and declarations of the Prophet Mohammad (PBUH) and those of his companions and their judgments, in addition to common sense and unanimity. It's also connected with major legislative rules such as: Innocence is origin (of dooms and Sureness shouldn't be ignored for the sake of uncertainty Suspicion might be in the basic elements of a crime or in means of proving it or in surrounding circumstances. Execution of the rule Punishments may be detained by Suspicions means that a ruler (judge) is responsible mainly for detection and being quite sure that a crime deserves its definite punishment; but if he found any suspicion in any basic factor such as being unintentional or the accused person was under age or may be obliged or forced to do so, or perhaps there were various aspects of legality or illegality of the deed or whether circumstances might have led to such deed, as thefts which happened in the (starvation year) or any suspicion in the way of proving a crime as being dependent on the accused confession if he later denies. In such cases a judge must drop the punishment completely or reduce it or change it to merely censure, and if it was a murder crime the accused shouldn't be sentenced to death but only to pay wergild (blood money). The legal rule Punishments may be detained by Suspicions doesn't mean the loss of people 's rights, so theft punishment might be forgiven but the thief should be forced to return the stolen things if they were still with him or guarantee them if lost. In case of murder crimes, wergild may be taken instead of sentence to death.

جرائم الحدود والقصاص جرائم خطيرة تمس كيان المجتمع ونظامه، لذا حدد الشارع مقادير العقوبات المترتبة على ارتكابها وجعلها في جرائم الحدود خاصة لا تقبل فيها شفاعة ولا إسقاط ولا تنازل، ومع هذا التشدد في تحديد المقادير وإلزامية التنفيذ إلا أنه في الوقت نفسه وضع من القواعد والضوابط ما يضمن عدم تطبيق هذه العقوبات إلا إذا كانت الجناية كاملة وثابتة ثبوتاً لا يدع مجالاً للشك في أن هذه الجريمة تستحق هذه العقوبة، ومن أوليات هذه القواعد قاعد ة" الحدود تدرأ بالشبهات". وهذه القاعدة متفق عليها عند جمهور الفقهاء ولم يخالف إلا الظاهرية، وهي مستندة إلى أقوال الرسول وأفعاله، وأقوال الصحابة رضوان الله عليهم وأقضيتهم بالإضافة إلى المعقول والإجماع. ويضاف إلى ذلك ارتباطها بكبريات القواعد الفقهية كقاعدة "الأصل براءة الذمة"، وقاعدة "اليقين لا يزول بالشك". والشبهة قد تكون في أركان الجريمة أو قد تكون في طرق إثباتها أو في الظروف المحيطة بها وتطبيق قاعدة "الحدود تدرأ بالشبهات" يعني: أن على الحاكم مسئولية كبيرة في التحري والتثبت من أن هذه الجريمة المرتكبة تستحق العقوبة الحدية ، فإذا ثبت لديه أن هناك شبهة في ركن من أركانها كأن لم تكن صادرة عن قصد من الجاني بأن كان صغيراّ أو مكرهاً، أو أن هذا الفعل المرتكب مختلف في حله وحرمته، أو أن الظروف العامة هي التي ألجأت إلى ارتكاب هذا الفعل كالسرقة في عام المجاعة، أو أن هناك شبهة في طريق إثباته كأن تكون وسيلة الإثبات هي الإقرار فيرجع عن إقراره، فإن من واجب الحاكم أن يعمل على إسقاط العقوبة الحدية بالكامل أو التخفيف منها وتحويلها من عقوبة حدية إلى عقوبة تعزيرية. وإن كانت الجريمة من جرائم القصاص لم يحكم به واكتفى بالدية. ودرء الحد بالشبهة لا يعني ضياع حقوق العباد: ففي حد السرقة قد يدرأ الحد ولكن لا يسقط حق إرجاع المال المسروق إن كان موجوداً أو ضمانه إن كان مستهلكاً، وفي جرائم الاعتداء على النفس أو ما دون النفس إن سقط القصاص للشبهة فلا تسقط الدية وهكذا.
الشبهة وأثرها في الحدود والقصاص